Effect of glucose on nitrogen removal and microbial community in anammox-denitrification system. (November 2017) - Qin, Yujie; Cao, Yan; Ren, Junyi; Wang, Tongyu; Han, Bin
Highlights: Simultaneous partial denitrification, anammox and denitrification were achieved. The optimal nitrogen removal was achieved at the influent glucose of 56.4 mg L −1 . Predominant genus changed with the variation of influent glucose concentration. Abstract: The effect of glucose on nitrogen removal and microbial communities in the anammox-denitrification systems was investigated. The optimal nitrogen removal could be achieved when the influent glucose concentration was 56.4 mg L −1 . The influent nitrite to ammonium ratio of 0.95–1.40 would not obviously affect the nitrogen removal due to the coexistence of anammox, denitrification and partial denitrification. The anammox activity was deteriorated with increasing glucose concentration. When the influent glucose concentration was increased to 374.9 mg L −1, the average ammonium removal efficiency decreased from 97% to around 10% and anammox activity was seriously inhibited. The anammox activity quickly recovered with decreasing influent glucose and increasing influent nitrite. High-throughput sequencing analysis suggested that the predominant genus changed from Candidatus Kuenenia to Diaphorobacter with the addition of glucose and then changed to Hydrogenophaga with the decrease of glucose. It indicated that organics concentration had an effect on the microbial communities.